Can Patient-Reported Outcomes Predict the Need for Secondary Surgeries After Hip Arthroscopy?. Issue 1 (January 2021) - Shapira, Jacob; Bheem, Rishika; Kyin, Cynthia; Rosinsky, Philip J.; Meghpara, Mitchell B.; Maldonado, David R.; Lall, Ajay C.; Domb, Benjamin G.
Background: Patient-reported outcomes (PROs) capture the postoperative period and reflect the patient's perspective of one's own recovery. However, it is unknown if PROs can reflect and predict the need for secondary surgeries after a primary hip arthroscopy. Purpose: To examine if PROs at 3 months and 1 year after primary hip arthroscopy were correlated with future reoperations and determine the critical thresholds for significant PROs utilizing a multivariate logistic regression analysis and receiver operator characteristic (ROC) analysis. Study Design: Case-control study; Level of evidence, 3. Methods: Data on consecutive patients who underwent primary hip arthroscopy between February 2008 and August 2018 was retrospectively reviewed. Patients were included for analysis if they had the following PROs preoperatively and at 3 months and 1 year postoperatively: modified Harris Hip Score (mHHS), Nonarthritic Hip Score (NAHS), and visual analog scale (VAS) for pain. Patients were split into 2 groups: those who underwent secondary surgery and those who did not. Patient variables, intraoperative labral treatment, preoperative PROs, and postoperative PROs were compared between the 2 groups. A multivariate logistic regression analysis and ROC analysis were deployed to evaluate the correlation between PROs and the need for future surgery. Results: A total of 911 primary arthroscopy cases were included in this study. While age, body mass index, labral treatment, and 3-month and 1-year follow-up mHHS, NAHS, and VAS were significant in the bivariate analysis, the multivariate logistic regression analysis only found 1-year mHHS to be significant in the final model ( P < .05). The ROC curve for 1-year mHHS demonstrated acceptable discrimination between patients requiring secondary surgery and patients not requiring secondary surgery with an area under the curve of 0.73. Using the Youden index, a threshold of 80.5 was determined for the 1-year mHHS. Conclusion: The risk for secondary procedures may be evaluated with mHHS at 1 year after primary hip arthroscopy. Surpassing a score of 80.5 may be associated with a 74.4% reduction in risk for either a revision hip arthroscopy or a conversion to hip replacement.